Speech rhythm as durational marking of prosodic heads and edges. Evidence from Catalan, English, and Spanish - Prieto, P; Vanrell, M; Astruc, L; Payne, E; Post, B (International Speech Communication Association, 2010)
Data from a total of 24 speakers reading 720 utterances from Catalan, English, and Spanish show that differences in rhythm metrics emerge even when syllable structure and vowel reduction are controlled for in the experimental materials, strongly suggesting that important differences in timing exist in these languages, and thus that the rhythmic percept is not solely dependent on these two phonological properties in a given language. Further analyses of the data indicate that the rhythmic class distinctions under consideration finely correlate with differences in the way languages instantiate two prosodic timing processes, namely durational marking of prosodic heads and prosodic edges. A prosody-based hypothesis is proposed regarding the importance of these durational patterns across languages for the perception of rhythmic contrasts.